Fertilization, Cleavage and Implation - Hayati, Lusia (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Most of the livestock in Indonesia are still conventional or traditional farms, where the quality of the seeds, the use oftechnology and the skills of farmers are still relatively low, thus affecting the productivity and genetic quality oflivestock. Therefore it is necessary to have knowledge about livestock reproduction that discusses fertilization,cleveage and implantation. Fertilization or fertilization (singami) is the fusion of two gametes which can be a nucleusor nucleus cells to form a single cell (zygote) or fusion of the nucleus. the process starts with the preparation of ovumcells and spermatozoa; penetration; core incorporation; and early zygote cleavage. Fertilization phase is the meetingbetween sperm cells and ovum cells and will produce zygote. Zygote will perform cell division (cleavage). The zygotethen undergoes growth and development through stages, namely division, gastrulation, and organogenesis.Implantation or also known as oxidation is the process of implanting the embryo, which is the result of conception,into the uterine wall (endometrium) to further develop.